2022
DOI: 10.1111/bcp.15172
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of elevated creatine phosphokinase between daptomycin alone and concomitant daptomycin and statins: A systematic review and meta‐analysis

Abstract: The present systematic review and meta-analysis evaluated the incidence of elevated creatine phosphokinase (CPK) levels between daptomycin alone and concomitant daptomycin and statin use. Methods:We searched the PubMed, Web of Sciences, Cochrane Library and ClinicalTrials.gov databases. We analysed the incidence of elevated CPK between daptomycin alone and concomitant daptomycin and statins among studies defining CPK elevation as levels ≥ the upper limit of normal (ULN) or ≥5Â ULN. We also analysed the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…A meta-analysis comparing the effects of daptomycin, a cyclic lipopeptide antibiotic, given alone or together with a statin, showed that the incidence of daptomycin-related rhabdomyolysis was significantly higher in patients taking a statin [ 34 ]. Similar results were reported in another meta-analysis [ 35 ]. It must be emphasised, however, that knowledge of the metabolism of concomitant drugs and possible interactions with statins always provides the opportunity to substitute the statin with another (usually a hydrophilic one that spares hepatic metabolism), reduce the statin dose (and/or concomitant therapy) and, depending on baseline cardiovascular risk, add a non-statin therapy that does not use the CYP P450 pathway and is very safe (ezetimibe, bempedoic acid and PCSK9-targeted therapy approach).…”
Section: Resultssupporting
confidence: 91%
“…A meta-analysis comparing the effects of daptomycin, a cyclic lipopeptide antibiotic, given alone or together with a statin, showed that the incidence of daptomycin-related rhabdomyolysis was significantly higher in patients taking a statin [ 34 ]. Similar results were reported in another meta-analysis [ 35 ]. It must be emphasised, however, that knowledge of the metabolism of concomitant drugs and possible interactions with statins always provides the opportunity to substitute the statin with another (usually a hydrophilic one that spares hepatic metabolism), reduce the statin dose (and/or concomitant therapy) and, depending on baseline cardiovascular risk, add a non-statin therapy that does not use the CYP P450 pathway and is very safe (ezetimibe, bempedoic acid and PCSK9-targeted therapy approach).…”
Section: Resultssupporting
confidence: 91%
“…Daptomycin-induced CPK elevation is considered to be dependent on trough concentration; therefore daptomycin at HDs should be used with caution. 18,40,41 In addition to trough concentration, other risk factors for daptomycin-induced CPK elevation include statins, antihistamines, obesity, history of rhabdomyolysis, baseline CPK levels and African American ancestry [42][43][44][45][46][47] ; however, their effect on safety was not evaluated in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…For instance, high levels of voriconazole induce hepatotoxicity, while toxicities associated with the prolonged use of ganciclovir include pancytopenia, neurotoxicity, and nephrotoxicity, all of them described as dose-independent effects [ 92 ]. In addition, a recent systematic review and meta-analysis concluded that daptomycin administration in OPAT patients under treatment with statins significantly increased the incidence of rhabdomyolysis caused by creatinine phosphokinase level elevation [ 93 ].…”
Section: Implementation Of An Opat Multidisciplinary Circuitmentioning
confidence: 99%